ANALYSIS OF ADOLESCENT INTERPERSONAL COMMUNICATION IN THE FILM DUA GARIS BIRU - Nurul Udhiyah Arifah Hamid; Ahmad Ismail (Jurnal Multidisipliner Kapalamada, 2026)
This study aims to analyze adolescent interpersonal communication as represented in the film Dua Garis Biru. The research employed a qualitative approach using content analysis to examine scenes, dialogues, and character interactions depicting adolescent communication dynamics. The analysis was based on interpersonal communication dimensions, including openness, empathy, supportiveness, positiveness, and equality. The findings indicate that interpersonal communication in the film is influenced by family communication patterns, emotional conditions, and individuals' abilities to convey and interpret messages. Most conflicts arise from limited openness and communication misunderstandings, while empathy, honesty, and family support play essential roles in conflict resolution. The film demonstrates that effective interpersonal communication contributes to mutual understanding, strengthens interpersonal relationships, and assists adolescents in dealing with various life challenges